PEMODELAN PENGARUH IKLIM TERHADAP ANGKA KEJADIAN DEMAM BERDARAH DI KOTA AMBON MENGGUNAKAN METODE REGRESI GENERALIZED POISSON - Kondo Lembang, Ferry; Nara, Eysye Alchi; Rumlawang, Francis Yunito; Talakua, Mozart Winston (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2019)
Dengue Hemorrhagic Fever (DHF) is one of the dreaded diseases of the transition season. DHF is a disease found in tropical and subtropical regions that caused by Dengue virus which is transmitted through Aedes mosquitoes. According to the World Health Organization (WHO) data, it is stated that Indonesia is the country with the highest dengue fever case in Southeast Asia. The incidence of dengue fever in Indonesia tends to increase in the middle of the rainy season, and one of the regions in Indonesia with the high level of rainfall intensity is Ambon City. DHF cases in Ambon city increase from year to year due to the last five years the intensity of rainfall is very high. Therefore, this study aims to identify climate factors that affect the incidence of DHF in Ambon City by using Generalized Poisson Regression method. Generalized Poisson Regression is appropriately considered to analyze the causing factors DHF incidence because the rating case of DHF is usually the count data that following the Poisson distribution. The results showed that the smallest AIC value for the Generalized Poisson Regression model was 75.842 with significant variables is DHF in the city of Ambon were one month earlier, air humidity, rainfall, and air humidity two months earlier.